2022
DOI: 10.3389/fpsyg.2022.831628
|View full text |Cite
|
Sign up to set email alerts
|

“A Group of Fellow Travellers Who Understand”: Interviews With Autistic People About Post-diagnostic Peer Support in Adulthood

Abstract: Receiving a diagnosis of autism in adulthood can be a life changing event, impacting identity, relationships, and mental health. A lack of post-diagnostic support has been highlighted by autistic adults, their allies, clinicians, and service providers. It can be a source of distress for autistic adults, reinforcing feelings of social isolation and rejection. Peer support could be a cost-effective, flexible, and sustainable model to provide community-based support for autistic adults. However, there is little r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…Non-gender specific autism research has highlighted the benefits of peer support and connectedness within the autistic community. 34 , 35 As well, gender-specific addiction treatment studies in non-autistic women have shown the value of women’s only treatments. 20 , 36 , 37 It has been suggested that women’s only group therapy can feel safer, more supportive and more comfortable, and allow women to discuss gender-specific concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Non-gender specific autism research has highlighted the benefits of peer support and connectedness within the autistic community. 34 , 35 As well, gender-specific addiction treatment studies in non-autistic women have shown the value of women’s only treatments. 20 , 36 , 37 It has been suggested that women’s only group therapy can feel safer, more supportive and more comfortable, and allow women to discuss gender-specific concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic work aimed at increasing selfcompassion could help autistic individuals reframe their struggles and develop a more positive selfconcept, with benefits for mental well-being (Cai & Brown, 2021). Furthermore, autistic people should be provided access to autistic-led spaces and communities where they feel safe and supported enough to unmask (Crane et al, 2021;Crompton et al, 2022). As autistic individuals often struggle to balance the tension between camouflaging and disclosure, clinicians could engage them in collaborative and supportive discussions, working through decisions about "whether, when, with whom, and for which purposes" they could camouflage or disclose (Loo et al, 2021, p. 33).…”
Section: Implications For Social Change and Clinical Practicementioning
confidence: 99%
“…In light of these difficulties, our participants expressed the need for peer support from other autistic parents. Recent research [64][65][66] has shown that peer support is an effective form of support. Supportive interaction with other autistic people also protects against the effects of minority stress and provides a sense of belonging 67 .…”
Section: Summary Of Findingsmentioning
confidence: 99%